Design of foldable PCBSat enabling three-axis attitude control. (March 2022) - Gong, Haoran; Gong, Shengping
Abstract: Satellite-on-a-printed circuit board (PCBSat) is a kind of femto-satellite that integrates all the electronic devices onto a PCB. Constrained by the energy/volume capacity, traditional attitude actuators no longer suit the PCBSat. In the paper, employing the flexible PCB material and micro-steppers, a new design that enables the PCBSat to fold and unfold is proposed, and a prototype is manufactured. The foldable PCBSat could achieve attitude maneuver by the spatial multibody dynamical effect. Meanwhile, the copper coils embedded in the boards can form a 3D magnetorquer when the PCBSat is at the orthogonal-fold status, making magnetic de-tumbling possible. Related theories combined with the detailed design of the PCBSat are introduced, and simulations are conducted to demonstrate the effectiveness of the attitude control mechanism. Highlights: A foldable PCBSat enabling attitude control is designed and a prototype is manufactured. Embedded coils in the boards could form a 3D magnetorquer when the PCBSat folds properly. Attitude maneuver could be achieved by alternative turns of the boards. Dynamic simulations are conducted to demonstrate the effectiveness of the attitude control mechanism.